Implementation of the Governor's Functions and Authorities in the Implementation of Government - Mirza Nasution; Herdi Munte (Faculty of Law, Universitas Pekalongan, 2025)
This study uses a normative legal research method with legislative, conceptual, and historical approaches through library research, as well as qualitative analysis of primary, secondary, and tertiary legal materials. The research results indicate that the Governor's functions and authority as the head of the region and representative of the central government at the provincial level reflect a strategic role in managing government, administering regional affairs based on the principle of autonomy, and overseeing national policies in the region. The Governor must align national policies with local needs, ensure the effectiveness of development programs, and bridge conflicts between regions. However, challenges such as imbalance in roles, complexity in intergovernmental relationships, and limitations in institutional and regulatory frameworks require strengthening institutional capacity and regulatory harmonization. In building synergy between the central and regional governments, the Governor plays an important role in facilitating cross-regional coordination, resolving conflicts of interest between regions, and maintaining alignment between central and regional development planning, so the success of decentralization and regional autonomy heavily depends on the Governor's ability to build effective communication and collaboration across different levels of government